Nucleophilic nitration of arynes by sodium nitrite and its multicomponent reaction leading to double-functionalized arenes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Organic Letters, 2016)
An unusual nucleophilic nitration of arynes by NaNO2 in the presence of water has been developed, and the concept was further demonstrated to accomplish a double functionalization of arynes using a multicomponent reaction protocol to synthesize pharmaceutically important (2-nitrophenyl)methanol derivatives. Such substitution ortho to -NO2 is difficult by other means. The reaction conditions are mild and avoid the use of strong acids, expensive transition metal catalysts, and additives.

Diversity-oriented synthesis of spiroannulated benzofuran-3-one scaffold of leptosphaerin C and congeners via aryne insertion - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
A concise synthesis of functionalized cyclohexenone-fused spirobenzofuran-3-ones under mild reaction conditions was developed. The reaction proceeds via insertion of aryne into the C-O bond followed by a regioselective intramolecular conjugate addition. The use of silyl-protected acid was crucial for the transformation. This protocol was successfully applied for the synthesis of leptosphaerin C core and its novel analogues.

Transition-metal-catalyzed reactions involving arynes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Synthesis-Stuttgart, 2018)
The plethora of transformations attainable by the transition-metal-catalyzed reactions of arynes has found immense contemporary interest in the scientific community. This review highlights the scope and importance of transition-metal-catalyzed aryne reactions in the field of synthetic organic chemistry reported to date. It covers transformations achieved by the combination of arynes and various transition metals, which provide a facile access to a biaryl motif, fused polycyclic aromatic compounds, different novel carbocycles, various heterocycles, and complex natural products. 1 Introduction 2 Insertion of Arynes 3 Annulation of Arynes 4 Cycloaddition of Arynes 5 Multicomponent Reactions of Arynes 6 Miscellaneous Reactions of Arynes 7 Total Synthesis of Natural Products Using Arynes 8 Conclusion
Keywords: annulation; arynes; Cycloaddition; Insertion; multicomponent; Natural products; Transition Metal